How to Test the Association Between Baseline Performance Level and the Modulatory Effects of Non-Invasive Brain Stimulation Techniques - Lega, Carlotta; Cattaneo, Luigi; Costantini, Giulio (Frontiers in Human Neuroscience, 2022)
Behavioral effects of non-invasive brain stimulation techniques (NIBS) can dramatically change as a function of different factors (e.g., stimulation intensity, timing of stimulation). In this framework, lately there has been a growing interest toward the importance of considering the inter-individual differences in baseline performance and how they are related with behavioral NIBS effects. However, assessing how baseline performance level is associated with behavioral effects of brain stimulation techniques raises up crucial methodological issues. How can we test whether the performance at baseline is predictive of the effects of NIBS, when NIBS effects themselves are estimated with reference to baseline performance? In this perspective article, we discuss the limitations connected to widely used strategies for the analysis of the association between baseline value and NIBS effects, and review solutions to properly address this type of question.